Non‐invasive telemedical care in heart failure patients and stroke: post hoc analysis of TIM‐HF and TIM‐HF2 trials - Serdar Tütüncü; Marcus Honold; Kerstin Koehler; Oliver Deckwart; Friedrich Koehler; Karl Georg Haeusler (ESC Heart Failure)
Abstract Aims Patients with chronic heart failure (CHF) have an increased risk of ischaemic stroke. We aimed to identify the incidence rate and factors associated with ischaemic stroke or transient ischaemic attack (TIA) in CHF patients as well as the impact of non‐invasive telemedical care (NITC) on acute stroke/TIA. Methods and results We retrospectively analysed baseline characteristics of 2248 CHF patients enrolled to the prospective multicentre Telemedical Interventional Monitoring in Heart Failure study (TIM‐HF) and Telemedical Interventional Management in Heart Failure II study (TIM‐HF2), randomizing New York Heart Association (NYHA) II/III patients 1:1 to NITC or standard of care. Hospitalizations due to acute ischaemic stroke or TIA during a follow‐up of 12 months were analysed. Old age, hyperlipidaemia, lower body mass index, and peripheral arterial occlusive disease (PAOD) were independently associated with present cerebrovascular disease on enrolment. The stroke/TIA rate was 1.5 per 100 patients‐years within 12 months after randomization (n = 32, 1.4%). Rate of stroke/TIA within 12 months was in the intervention group similar compared with the control group (50.0% vs. 49.8%; P = 0.98) despite that the rate of newly detected atrial fibrillation (AF) was higher in the intervention group (14.1% vs. 1.6%; P < 0.001). A history of PAOD (OR 2.7, 95% CI 1.2–6.2; P = 0.02) and the highest tertile (OR 3.0, 95% CI 1.1–8.3) of N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) on enrolment were associated with stroke/TIA during follow‐up. In patients who suffered acute stroke or TIA during follow‐up, echocardiography was part of the diagnostic workup in only 56% after hospital admission. Conclusions Annual rate of ischaemic stroke/TIA in NYHA II/III patients is low but higher in those with elevated NT‐proBNP levels and history of PAOD at baseline. NITC showed no impact on the stroke rate during 1 year follow‐up despite a significantly higher rate of newly detected AF. Irrespective of known CHF, echocardiography was often missing during in‐hospital diagnostic workup after acute stroke/TIA.